2001
DOI: 10.1063/1.1396829
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ultraviolet photoconductivity in semiconducting ZnGa2O4 thin films

Abstract: We have investigated the conductivity and photoconductivity response of undoped and Li-doped ZnGa2O4 epitaxial films grown using pulsed-laser deposition. A significant enhancement of the ultraviolet (UV) photoresponse is observed with Li doping that also correlates with an enhanced luminescent intensity. The wavelength dependence observed for creation of free carriers under UV excitation suggests that the transition is either band-to-band or involves a defect level near the band edge. Moderate n-type dark cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…Zinc gallate (ZnGa 2 O 4 ) phosphor has attracted enormous attention recently, because ZnGa 2 O 4 is an attractive phosphor host candidate material for vacuum florescent displays and electroluminescence displays due to its favorable cathodoluminescence (CL) and photoluminescence (PL) properties, and thermal stability [1,2]. With a band gap of 4.4 eV, ZnGa 2 O 4 exhibits a blue luminescence under excitation by low voltage electrons (30 V d.c) or ultraviolet light [3].…”
Section: Introductionmentioning
confidence: 99%
“…Zinc gallate (ZnGa 2 O 4 ) phosphor has attracted enormous attention recently, because ZnGa 2 O 4 is an attractive phosphor host candidate material for vacuum florescent displays and electroluminescence displays due to its favorable cathodoluminescence (CL) and photoluminescence (PL) properties, and thermal stability [1,2]. With a band gap of 4.4 eV, ZnGa 2 O 4 exhibits a blue luminescence under excitation by low voltage electrons (30 V d.c) or ultraviolet light [3].…”
Section: Introductionmentioning
confidence: 99%
“…1(d)shows the SAED pattern of the interface, from which the interfacial layer was identified as a cubic structural ZnGa 2 O 4 layer, ½101 c ==½1 210 h , with the hexagonal wurtzite structrual ZnO and GaN. The ZnGa 2 O 4 was characterized as a wider band gap material (with a band gap of 4.4-5.0 eV) than those of ZnO and GaN according to literature reports 12,19. The forming of ZnGa 2 O 4 revealed that some defects like oxygen vacancies (V O ) or gallium vacancies (V Ga ) should be introduced to ZnO or GaN especially near the interfacial layer during the thermal annealing.…”
mentioning
confidence: 97%
“…Compounds in this family usually have wide band gaps and are attractive in theory and experiments for better understanding of their physical properties [1][2][3][4]. In the normal spinel with cubic symmetry (space group Fd-3m), the A atoms occupy the center of tetrahedral sites and the B atoms occupy the center of octahedral sites.…”
Section: Introductionmentioning
confidence: 99%